1996
DOI: 10.1136/adc.75.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in paediatric asthma and cystic fibrosis.

Abstract: Nitric oxide (NO) is present in exhaled air ofhumans. This NO is mostly produced in the upper airways, whereas basal NO excretion in the lower airways is low. Children with Kartagener's syndrome have an almost total lack of NO in nasally derived air, whereas adult asthmatics have increased NO in orally exhaled air. NO excretion was measured in the nasal cavity and in orally exhaled air in 19 healthy children, in 36 age matched subjects with asthma, and in eight children with cystic fibrosis. NO levels in orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
183
6
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(215 citation statements)
references
References 15 publications
25
183
6
1
Order By: Relevance
“…The initial NO value obtained with the balloon method in the present study was slightly lower than values obtained previously in healthy children with the same sampling method [35]. Other studies also reported exhaled NO levels in CF-subjects that were not higher than in control subjects [18,19,34]. Whether this finding reflects reduced diffusion and metabolism of NO within the viscous airway secretions or a genuine reduction in airway mucosal NO synthesis is not clear.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The initial NO value obtained with the balloon method in the present study was slightly lower than values obtained previously in healthy children with the same sampling method [35]. Other studies also reported exhaled NO levels in CF-subjects that were not higher than in control subjects [18,19,34]. Whether this finding reflects reduced diffusion and metabolism of NO within the viscous airway secretions or a genuine reduction in airway mucosal NO synthesis is not clear.…”
Section: Discussioncontrasting
confidence: 54%
“…Exhaled nitric oxide (NO) has been put forward as another noninvasive marker of airway inflammation [16,17]. However, in stable CF-patients orally exhaled NO levels are not elevated [18,19]. Data in children on NO and H 2 O 2 during acute infectious respiratory tract exacerbation in CF are lacking.…”
mentioning
confidence: 99%
“…In allergic rhinitis the picture is less clear. Some groups have shown an increase in nasal NO in rhinitis [26][27][28], while others find normal values in these patients [24,29,30]. The reason for the discrepancies in studies on rhinitis is probably related to methodology.…”
Section: Discussionmentioning
confidence: 96%
“…For example, nasal NO is extremely low in primary ciliary dyskinesia (PCD) [4] and in cystic fibrosis [24]. In fact, a nasal NO test is currently part of the clinical routine at the national centre for PCD in the UK [25].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that air speed will have to be taken into consideration in future nasal NO measurements and that different methods at different volume flow rates measure different aspects of nasal NO release. Interestingly, two studies on allergic rhinitis show an increase in nasal NO [6,27], while two show no difference in nasal NO [7,12].…”
Section: Discussionmentioning
confidence: 99%